Characterisation of the biological response of Saccharomyces cerevisiae to the loss of an allele of the eukaryotic initiation factor 4A - Venturi, Veronica; Little, Richard; Bircham, Peter W.; Rodigheri Brito, Juliana; Atkinson, Paul H.; Maass, David R.; Teesdale-Spittle, Paul H. (Biochemical and biophysical research communications, 2018)
The translation initiation machinery is emerging as an important target for therapeutic intervention, with potential in the treatment of cancer, viral infections, and muscle wasting. Amongst the targets for pharmacological control of translation initiation is the eukaryotic initiation factor 4A (eIF4A), an RNA helicase that is essential for cap-dependent translation initiation. We set out to explore the system-wide impact of a reduction of functional eIF4A. To this end, we investigated the effect of deletion of TIF1, one of the duplicate genes that produce eIF4A in yeast, through synthetic genetic array interactions and system-wide changes in GFP-tagged protein abundances. We show that there is a biological response to deletion of the TIF1 gene that extends through the proteostasis network. Effects of the deletion are apparent in processes as distributed as chromatin remodelling, ribosome biogenesis, amino acid metabolism, and protein trafficking. The results from this study identify protein complexes and pathways that will make ideal targets for combination therapies with eIF4A inhibitors.